Levels of citizen competencies in university students of health sciences - Mescua Figueroa, Augusto César (2020)
Professional training should aim to integrate educational processes that include the development of technical skills and citizen competencies in the perspective of professional practice that leads to acting in favor of the common good and public good, from the perspective of citizen duties and rights. The research aimed to determine the levels and predominance of citizenship competencies in university students of health sciences. It included the descriptive, non-experimental design and cross-sectional level. The sample was 210 Peruvian health sciences students from Metropolitan Lima. A questionnaire of multiple questions and a Likert scale was applied. As a result, it was identified that more than half of the students were at a medium level and the others at a high or low level. It was concluded that emotional skills are the most predominant and that communication, cognitive (critical thinking) and citizenship skills (knowledge of duties and rights of citizens) require further development and treatment in the curricular programs of professional training.